Modified Two-Flap Palatoplasty With Leaving Lateral Periosteum and Application of Honey Pack : A Preliminary Study - Bangun, Kristaninta; Sudjatmiko, Gentur; Mahandaru, Danu (Jurnal Plastik Rekonstruksi, 2012)
According to our experience in Ciptomangunkusumo hospital, most cleft palate patients has wide gap. It makes the epithelialization of the lateral defect takes longer time ( 3- 4 weeks). In this study, the authors propose a modified technique to the two-flap palatoplasty by not elevating the lateral part of the periosteum with the flap, and then apply honey packs to cover the lateral defects. The technique modification and additional honey-soaked dressing are expected to hasten the epithelialization rate. Twelve consecutive patients with non-syndromic cleft palate (with or without cleft lip) are included in the study. They undergo the modified two-flap palatoplasty with the lateral periosteum left behind, covering the palatal bone and the utilization of Honey pack. The rate of epithelialization is then observed every 2 days after operation until full healing is achieved. Complete epithelialization was attained within 5 days in one patient ( 2,8 mm/day), within 7 days in 8 patients (2-2,5mm/day), and within 9 days in 3 patients (2,2-2,7mm/day). There were no surgical complications, such as hemorrhage or wound infection. The fistula of the palate was not found until the defect closed. Our technique hasten the rate of epithelialization. It may prevent the maxillary growth disturbances in the future because faster healing reduces scar formation and wound contraction.